Phenylethanoid glycosides of Phlomis younghusbandii Mukerjee ameliorate acute hypobaric hypoxia-induced brain impairment in rats. (April 2019) - Luan, Fei; Li, Maoxing; Han, Keqing; Ma, Qiang; Wang, Jian; Qiu, Yan; Yu, Linhong; He, Xirui; Liu, Daoheng; Lv, Haizhen
Highlights: We investigated the effects of PhGCs isolated from the roots of Phlomis younghusbandii on high altitude cerebral edema rats. PhGCs suppressed the inflammatory response and oxidative stress in acute hypobaric hypoxia (AHH)-stimulated high altitude cerebral edema rats. PhGCs inhibited the relative expression of NF-κB-mediated inflammatory cytokines induced by acute hypobaric hypoxia. These results demonstrate that PhGCs is a potential therapeutic candidate in the treatment of HACE diseases. Abstract: High altitude cerebral edema (HACE), whose development process is associated with oxidative stress and inflammatory response, is a life-threatening condition caused by rapid ascent speed to high altitudes. Phenylethanoid glycosides (PhGCs) are primary active constituents isolated from Phlomis younghusbandii Mukerjee that reportedly exhibit potent anti-oxidant and anti-inflammatory activities. The present study aims to investigate the protective effect of phenylethanoid glycosides (PhGCs) from P. younghusbandii in acute hypobaric hypoxia (AHH) – stimulated HACE rats and its underlying mechanisms. The expression of pro-inflammatory cytokine levels (IL-1β, TNF-α, and IL-6) was detected by RT-PCR and ELISA at mRNA and protein levels in brain tissues. Western blotting was carried out to measure the major protein levels (IL-1β, TNF-α, and NF-κB) in brain tissues. The oxidative stress biomarkers (MDA, SOD, and GSH) were evaluated using kits. Results demonstrate that PhGCs significantly improved pathological changes in brain tissues, reduced the brain's water content, and attenuated the production and mRNA expression of pro-inflammatory cytokines. Furthermore, the increased oxidative stress and the decrease in anti-oxidant stress system under the AHH condition were also abrogated reversely through PhGCs treatment by elevating the levels of SOD and GSH and suppressing the accumulation of MDA. Simultaneously, there was also a significant reduction in NF-κB, IL-1β, and TNF-α protein expression levels in brain tissues, suggesting that blocking the NF-κB signaling pathway activation prevented the production of pro-inflammatory cytokines. Taken together, these findings indicate that PhGCs may afford a protectively intervene in HACE through the suppression of oxidative stress and inflammatory response via the inhibition of the NF-κB signaling pathway, indicating that PhGCs are promising agents for the treatment of acute HACE.